URUTAN KLAUSA DALAM KALIMAT MAJEMUK SUBORDINATIF BAHASA INDONESIA: KAJIAN DARI PERSPEKTIF SINTAKSIS DAN WACANA - I Praptomo Baryadi (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2007)
This paper reports the research result on the order of clauses in subordinative compound sentences in Indonesian from the syntactic and discourse perspectives. There are two types of clause orders in the subordinative compound sentences, namely, (i) lower clauses on the right side of the main clauses, and (ii) lower clauses on the left side of the main clauses. From the syntactic view, lower clauses on the right side of the main clauses may occupy the syntactic functions of O, Complement, S, and Adverbial, while the lower clauses on the left of the main clauses only occupy the function of Adverbials. From the discourse level, lower clauses on the right side of the main clauses only contain information related to the information of the main clauses and not directly connected to the information of the preceding sentence. On the other hand, lower clauses on the left side of the main clauses contain textual presupposition, i.e containing repeated information from the preceding sentence Thus, lower clauses on the left side of the main clause contain old information. The result of the study also proves the truth of Ramsey hyphotesis (1987:385) stating that lower clauses preceding the main clauses have a broader scope as compared to the preceding uterance while those following the main clauses have a more localized scope, i.e, merely related to the main clause.